Exploring the Potential of Artificial Intelligence (AI) as a Pedagogical Tool in Education: Students’ Perceptions. - Yélamos-Guerra, María Salomé (My University, 2025)
The use of AI is becoming something common in education among students at all levels. In our 21st century technological society digital natives feel comfortable using this new tool. Besides, the advances of AI are unstoppable and move at a very fast pace: “Artificial Intelligence (AI) has grown rapidly in recent years making its way into various industries and sectors. The education sector is also not being left behind” (Zainuddin et al. 2024, 907). AI can bring benefits to both teachers and students if used appropriately, bearing in mind that it can be used as a support in the students’ assignments as it facilitates the learning process mediated by technology (Fitria 2021). It is almost essential to integrate AI technology into the educational field, especially in Higher Education where students are tasked with numerous written assignments and normally feel the urge to use this tool. So, it might be interesting to delve into this topic and the students’ perception about the use of AI. In the AI era it is paramount for teachers to show students how to properly use this powerful tool considering that AI also raises ethical issues in the educational setting so, guidelines need to be established for its implementation in the education field (Bazoukis et al. 2024). In the present study, conducted during the academic year 2024/2025, students were asked about the use of AI and its possible implementation as a pedagogical tool. The participants were undergraduate and master’s students at the University of Málaga, representing both the Faculty of Education and the Faculty of Humanities. The general objectives of this study were, first, to examine students’ perception on the use of AI and second, to determine their opinion on the use of AI as a pedagogical tool in their future teaching careers. The students’ opinions were analysed and measured through a questionnaire, which was elaborated ad hoc and properly validated. The obtained results were highly positive being the students’ opinions mostly favourable to the use of AI in general. The study also reveals great acceptance on the part of the students to the use of AI in their future role as teachers. Further research is required to assess the sustainability and impact of such practices within classroom environments, even at other educational levels like primary and secondary education, where the need for AI integration is also critical. Both students and teachers need to learn how to use this powerful tool proficiently.
Keywords: Inteligencia artificial en la enseñanza; Enseñanza superior; Tecnología educativa; Artificial Intelligence (AI); Higher Education; Technology; Students; Pedagogical tool